Causative organisms and visual prognosis of endophthalmitis in Cairo University Hospitals, Cairo, Egypt - Nermeen M Bahgat; Mona K Ibrahim; Ahmed Awadein; Gihan M Shokier (Delta Journal of Ophthalmology, 2023)
Purpose The aim of this study was to identify the most common causative organisms, treatment modalities, and visual prognosis of cases of endophthalmitis in Cairo University Hospitals, Cairo, Egypt. Patients and methods This was a prospective study that was carried out on consecutive patients presenting with exogenous endophthalmitis to Cairo University Hospital Casualty Unit, Cairo, Egypt, during the period from June 2021 to February 2022. Demographic and clinical characteristics of all patients were collected and analyzed. Vitreous tap was obtained from all patients and cultured. Treatment modalities were tabulated and analyzed. Factors influencing the final visual outcome were studied. Results The study included 31 eyes of 31 patients, with a mean age of 41.8±17.9 years (range=8–69 years). All cases had exogenous endophthalmitis, where 17 were postoperative, 12 posttraumatic, and two postintravitreal injection. Positive vitreous culture was detected in only nine (29%) patients. The most commonly identified organism was Streptococcus pneumoniae (four of nine patients, 44.4%). Cultures were positive for fungi in only two patients. Cultures were positive in 35% of postoperative endophthalmitis and in 25% of posttraumatic endophthalmitis. Treatment modalities included intravitreal antibiotics only (n=15; 48.4%), intravitreal antibiotics and delayed vitrectomy (n=8; 25.8%), immediate vitrectomy (n=7; 22.6%), and evisceration (n=1; 3.2%). The mean follow-up after presentation was 5.1±1.6 months (range=3–9 months). The factors associated with poor visual outcome were older age (P=0.032), history of ocular trauma (P<0.001), early presentation after trauma (P=0.021), and presence of corneal infection (P=0.001). The visual outcome was significantly better in those who had vitrectomy either immediately or after intravitreal injection (P=0.004). Conclusion S. pneumoniae was the most commonly identified organism in exogenous endophthalmitis in Cairo University Hospitals. Early vitrectomy and absence of corneal infection were associated with better visual outcome.